2009
DOI: 10.1017/s0924270800032798
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cholesterol and metabolic syndrome between bipolar disorder men with and without suicide attempts

Abstract: Patient with mental illnesses such as schizophrenia and bipolar disorder have an increased prevalence of metabolic syndrome (MetS) and its components compared to general population. Among psychiatric disorders, bipolar disorder ranks highest in suicidality with a relative risk ratio of completed suicide of about 25 compared to the general population.Regarding the biological hypotheses of suicidality, low blood cholesterol level has been extensively explored, although results are still conflicting. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
1
17
1
1
Order By: Relevance
“…However, since ours is a cross-sectional study, we cannot rule out that the use of anticonvulsant drugs, which were more prevalent in the non-attempter group, contributed to the discrepancy observed in BMI and serum triglyceride levels. In another study regarding BD, decreased cholesterol and triglycerides were observed in suicide attempters (Vuksan-Cusa et al, 2009). Interestingly, in Vuksan-Cusa's study the sample was free of psychotropic medication, reinforcing the idea that medication is not the sole contributor to changes in lipid profile.…”
Section: Discussionmentioning
confidence: 91%
“…However, since ours is a cross-sectional study, we cannot rule out that the use of anticonvulsant drugs, which were more prevalent in the non-attempter group, contributed to the discrepancy observed in BMI and serum triglyceride levels. In another study regarding BD, decreased cholesterol and triglycerides were observed in suicide attempters (Vuksan-Cusa et al, 2009). Interestingly, in Vuksan-Cusa's study the sample was free of psychotropic medication, reinforcing the idea that medication is not the sole contributor to changes in lipid profile.…”
Section: Discussionmentioning
confidence: 91%
“…Patients with bipolar disorder and lower cholesterol levels have a higher burden of manic-but not depressive-symptoms, suggesting a possible relationship between low cholesterol and manic morbidity [41] without an expected increased risk for vascular disease. Low levels of cholesterol and triglycerides also have been associated with more frequent suicide attempts in individuals with bipolar disorder, whereas the presence of the metabolic syndrome has been associated with fewer attempts [42]. Meanwhile, high triglycerides and the metabolic syndrome may predispose individuals to vascular disease.…”
Section: Mechanisms Leading To Elevated Cardiovascular Riskmentioning
confidence: 99%
“…Zhang et al, 2005), case-control (e.g. Vuksan-Cusa et al, 2009) and cohort studies (e.g Boscarino et al, 2009). Among the few studies that differentiate the fractions of cholesterol, suicidal behavior and impulsivity have been associated with lower levels of low-density lipoprotein/cholesterol (Lee and Kim, 2003;Agargun et al, 2004;Garland et al, 2007;Marcinko et al, 2008), while low levels of high-density lipoprotein/cholesterol have been more strongly associated with depressive symptomatology (Troisi, 2009).…”
Section: Low Serum Cholesterol and Suicidal Behaviormentioning
confidence: 99%